Student-Athlete Feedback on The 2023 Student Athletic Championships - Khuddus, Lutfhi Abdil; Yuhantini, Eva Ferdita; Supriyanto, Catur; Prabowo, Suryanto Agung; Bahauddin, Muhammad Arja; Sulistyana, Caturia Sasti (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
Sports are one of the means of shaping individual and collective character and national spirit. One of the Student Athletics Championship events is a school-level athletic competition to find potential seeds in Indonesia ranging from elementary to high school students. This competition is held starting from regional qualifications to the National Championship. Participants who participated were 32,000 from more than 200 schools and the most participants came from East Java, namely 5104 participants. This study aims to determine the athletes’ thoughts on the Student Athletics Championship event in assessing the negative and positive impacts of the event. The research design used was descriptive cross-sectional with a survey method of 71 athletic athletes selected by random sampling. The study was conducted at the Thor Field, Surabaya in March-October 2024. The instrument used was a post-event survey question with 4 question perspectives, namely the level of satisfaction with the initial stage of organizing the event, belief in the benefits of participating in the event, the level of satisfaction with the final stage of assessment and reward-giving, and plans and recommendations to friends or relatives to participate in the next event. The data analysis used in this study was descriptive. The study results showed that most athletes had a positive perception of participating in the 2023 SAC event and believed they would participate and recommend the next SAC event with an average of 97% (69 athletes). Athletes who participated stated that the 2023 SAC.